Social comparison and big-fish-little-pond effects on self-concept and other self-belief constructs: Role of generalized and specific others - Marsh, H; Trautwein, U; Luedtke, O; Koeller, O (2008)
Two studies integrate the big-fish-little-pond effect (BFLPE; negative effects of class-average achievement on academic self-concept, ASC), which is based upon educational psychological research, with related social psychological research that is based on social comparison theory. Critical distinctions are the nature of the social comparison processes that are based on generalized-other (class- or school-average) or individual (target comparison classmate) comparisons, and the nature of self-belief constructs that invoke normative (social comparison) or absolute frames of reference. In a large cross-national study (26 countries; 3,851 schools; 103,558 students), school-average ability negatively affected ASC but had little effect on 4 other self-belief constructs that did not invoke social comparison processes. In Study 2 (64 classes; 764 students), 2 sources of social comparison information (class-average achievement and achievement of an individually selected target comparison classmate) each had distinct, substantial negative effects on agency self-beliefs that invoked social comparison processes but not on metacognitive responses that did not invoke these processes. © 2008 American Psychological Association.